El tratamiento de la Prehistoria en Twitter: una aproximación a los afectos desde R - Vélaz Ciaurriz, David (Archeologia e Calcolatori, 2025)
This work aims to investigate the feelings and emotions that Prehistory generates in the social network Twitter (today called X) . To do this, the messages that, during a period of one year, contain the hashtag #prehistory, together with its possible variants, have been considered. The analysis has been carried out from an R programming environment, mainly through the Syuzhet library, that allows extrapolating feelings and emotions that underlie texts. However, the methodological proposal made in this paper is susceptible to being applied to different data samples related to other cultural manifestations or assets. From the point of view of the results obtained, it can be stated that the valence underlying the data sample analyzed can be considered as markedly positive. Regarding emotions, there is a predominance of anticipation and trust, followed by joy according to the model proposed by Plutchick, which is the one used in this work.
Keywords: Lenguaje R, Sentimientos, Emociones, Prehistoria; Lenguaje R; sentimientos; emociones; Prehistoria